2011
DOI: 10.1007/s11250-011-9862-9
|View full text |Cite
|
Sign up to set email alerts
|

Wool characteristics in the third generation of Arkharmerino × Ghezel and Arkharmerino × Moghani crossbreed sheep

Abstract: This investigation was conducted to evaluate the comparative productive performances and effect of some environmental factors on wool characteristics of Arkharmerino × Ghezel (Ar × Gh) and Arkharmerino × Moghani (Ar × Mo) crossbreed sheep. The mid-side fleece samples taken from animals during 2 years (2007-2008) were analyzed. Each sample was measured for average fiber diameter, fiber diameter variability, staple length, proportion of medullated fiber, proportion of kemp, and comfort factor. The comparative va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 20 publications
(35 reference statements)
2
7
0
Order By: Relevance
“…There was significant difference in the percentage of coefficient of variation of fiber diameter between different sexes, ages and breeds of sheep. A significant effect of sex on coefficient of variation of fiber diameter in sheep of current study is in agreement with the results found in Naeini sheep (Dashab et al, 2006) and Arkhamerino × Ghezel and Arkhamerino × Moghani crossbred sheep (Esfandyari et al, 2011). The impact of sex on coefficient of variation of fiber diameter could be associated with hormonal differences between both sexes.…”
Section: Mean Fiber Diameter and Staple Lengthsupporting
confidence: 92%
See 1 more Smart Citation
“…There was significant difference in the percentage of coefficient of variation of fiber diameter between different sexes, ages and breeds of sheep. A significant effect of sex on coefficient of variation of fiber diameter in sheep of current study is in agreement with the results found in Naeini sheep (Dashab et al, 2006) and Arkhamerino × Ghezel and Arkhamerino × Moghani crossbred sheep (Esfandyari et al, 2011). The impact of sex on coefficient of variation of fiber diameter could be associated with hormonal differences between both sexes.…”
Section: Mean Fiber Diameter and Staple Lengthsupporting
confidence: 92%
“…The 9.8% medullated OCF in the present study is similar to that reported for Arabi (10.9%) (Ashmawi & El-Azzawy, 1980), lower than those in the Awassi sheep in Jordan and Iraq (12%) (Tabbaa et al, 2001), Moghani sheep in Iran (18.36%) (Farahvash et al, 2010) and higher than those in the Ossimi (5.3%) and Rahmani (2.3%) sheep (Maria et al, 1992), Arkhamerino × Ghezel and Arkhamerino × Moghani crossbred sheep (7.1% and 8.1% respectively) (Esfandyari et al, 2011), Ghezel sheep (9.42%) (Farahvash et al, 2010). Proportion of medullated fiber in fine wool breeds is about 0.1%-0.5% (Lupton et al, 2004).…”
Section: Yield and Percentage Of Wool Typessupporting
confidence: 84%
“…Several crossing experiments in sheep are currently in progress, most of which are based on local breeds. It is expected that crossbreeding can lead to combination of favorable characteristics from Arkhar Merino (Rafat and Shodja, 2010;Esfandyari et al 2011). However, there is no information on the reproductive performance of these crossbred rams.…”
Section: Introductionmentioning
confidence: 99%
“…Significant effects of birth type on weight and fleece traits have previously been reported in other sheep breeds, such as Afrino (Snyman et al, 1995), Merino (Rose and Pepper, 1996), and Arkharmerino (Esfandyari et al, 2011). Birth type influenced traits mainly in immature animals, and significantly affected GFW1, GFW5, BW6, BW9, and BW12 (P < 0.001).…”
Section: Fixed Effectsmentioning
confidence: 69%